Deashing macroalgae biomass by pulsed electric field treatment. (May 2018) - Robin, Arthur; Sack, Martin; Israel, Alvaro; Frey, Wolfgang; Müller, Georg; Golberg, Alexander
Highlights: Ash content is a major hurdle for biomass processing notably for biofuel production. Current treatments are not environment-friendly and/or relevant for industry. Pulsed Electric Field (PEF) was used to enhance biomass ash removal by pressing. The enhanced treatment leads to a twofold increase in ash extraction. PEF significantly improved the extraction of major ash elements: K, Mg, P, Na, and S. Abstract: Among all biomass constituents, the ashes are major hurdles for biomass processing. Ashes currently have low market value and can make a non-negligible fraction of the biomass dry weight significantly impacting its further processing by degrading equipment, lowering process yield, inhibiting reactions and decreasing products qualities. However, most of the current treatments for deashing biomass are of poor efficiency or industrial relevance. This work is the first report on the use of Pulsed Electric Field (PEF) to enhance deashing of biomass from a high ash content green marine macroalga, Ulva sp., using hydraulic pressing. By inducing cell permeabilization of the fresh biomass, PEF was able to enhance the ash extraction from 18.4% (non-treated control) to 37.4% of the total ash content in average, significantly enhancing the extraction of five of the major ash elements (K, Mg, Na, P and S) compared to pressing alone.